Study on Kinetics of Self-diffusion Reaction by Application of 82Br as a Radioactive Tracer Isotope - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2016)
The kinetics of ion-isotopic self-diffusion reaction was studied by using radioactive 82Br as a tracer isotope as to study the effect of exchangeable ion concentration in the exchanger phase and that in solution. The effect of exchangeable ion concentration in the exchanger phase was studied by varying the amount of labelled ion exchange resins from 0.250 to 0.750 g, using fixed ionic concentration of 0.0 I M bromide ions in solution at a constant temperature of 27°C. The effect of ionic concentrations in solution was studied by varying the concentration of bromide ions in solution from 0.0025 to 0.02 M and by keeping the exchangeable ion concentration on the exchanger phase constant (0.5 g of labelled ion exchange resins), at 27°C.